Floral Motifs Design on Sarawak Traditional Malay Songket - Asrul Asshadi, Mohamad Morni; Mohd Azhar, Samin; Rafeah, Legino (2021)
This study is partly an ongoing project to identify the floral motifs design on Sarawak traditional Malay songket. This project begins with a review of related literature that provides an example of textile—also supported with visual data on Sarawak traditional Malay songket gathered from the field visit, which is captured into the digital compilation. The identification process defined that the Sarawak traditional Malay songket motifs mainly develop from various floral sources reflecting and inspiring nature. This study shared different design Malay songket motifs in Sarawak and represent their tradition in textile heritage.